Pelatihan Pembuatan Sabun Cuci Piring Bagi Suku Sakai di Desa Libo Jaya Siak Riau - Herispon, Herispon; Harwina, Yulia; Hendrayani, Hendrayani; Fachri, Rizqi; Yapentra, Arhipen; Anuar, Saiful; Kurniawan, Tengku Reza; Rofidah, Siti (Jurnal Pengabdian Masyarakat Akademisi, 2024)
Using the activity "training in making liquid dishwashing soap for women from the Sakai tribe in Libo Jaya Village, Kandis Siak, Riau with the aim of being able to use it themselves or sell it to support the family economy by making the best use of their free time filled with activities that are useful and have economic value" as part of the community service (PKM) program. The ladies of the Sakai tribe were the target of Community Service Activities (PKM) on July 26, 2023, pertaining to "Dish Washing Soap Making". The purpose of organizing this PKM is to encourage Sakai tribal women, disseminate information on the production of liquid dishwashing soap, and discuss ways to raise the economic standing of the family